ELatrine: Lessons Learned from the Development of a Low-Tech MFC Based on Cardboard Electrodes for the Treatment of Human Feces. Issue 3 (1st January 2017) - Kretzschmar, Jörg; Riedl, Sebastian; Brown, Robert Keith; Schröder, Uwe; Harnisch, Falk
Abstract : The aim of the study was to provide experimental proof-of-concept that stand-alone power generation based on microbial fuel cells (MFCs) operated using human feces as the substrate can be achieved. A pit latrine that is typically employed for decentralized treatment of human feces e.g. in regions without access to centralized wastewater infrastructures was installed as sampling site. It was the philosophy that the components, i.e. anodes and cathodes, used in the MFCs had to be based on low-cost precursors. This was achieved by recycling common household materials or waste products and a low-tech/cost production method was developed to convert them into usable electrodes. It is demonstrated that i) pre-tests on using an equivalent to vent-air from ovens or fire-places allowed a low-tech carbonization of e.g. corrugated cardboard to electrode materials; ii) that anodes based on corrugated cardboard can be operated using real human feces as substrate, nevertheless, providing only low current densities (15.09 ± 5.18 μA cm −2 ) and iii) cathodes – with nitrogen functionalities derived from (artificial) urine – based on corrugated cardboard or as an alternative jeans cloth show a good oxygen reduction reaction (ORR) activity. Introducing nitrogen containing surface moieties to the cathode surface increased the ORR up to factor 5 (chronoamperometry at 0 V vs. Ag/AgCl sat. KCl) compared to the untreated reference. Most importantly, highly valuable lessons for exploiting real and highly heterogeneous and dense substrates like human feces in microbial electrochemical technologies were learned.